Determining the influence of wetland drainage on baseflow in a high-elevation, snowmelt-dominated, headwater watershed, Senator Beck Basin, San Juan Mountains, SW Colorado - Chohan, Nicholas Patrick, author; Sanford, William E., advisor; Fassnacht, Steven R., committee member; Rugenstein, Jeremy C., committee member (Colorado State University. Libraries, 2025)
Mountain wetlands may be important for modulating groundwater discharge to streams in high-elevation, snowmelt-dominated, headwater watersheds, particularly in the dry season after snowmelt, when streamflow is at an annual low. While the basic mechanisms of water release from wetlands to streams (hereafter, termed as wetland drainage) are understood, the regional importance of wetland drainage in snowmelt-dominated mountain watersheds and its response to potential changes in climate are unknown. Decreases to winter snowpacks and changes to snowmelt regimes may reduce the volume of water stored in the subsurface available for supporting wetlands and baseflow, diminishing the influence of wetland drainage on streamflow. The goal of this study was to investigate the role and relative importance of wetland drainage on streamflow in the Senator Beck Basin (SBB), a small, high-elevation, snowmelt- dominated, headwater watershed, located in the San Juan Mountains of southwestern Colorado. The SBB has a single groundwater-supported wetland adjacent to the stream near the watershed outlet, making it an ideal place to study the effects of wetland drainage on streamflow. Wetland drainage, conceptualized as a component of baseflow, has been observed during several summers in the SBB, providing an important component of streamflow when other sources could not. Data from the SBB were used to estimate baseflow discharge using the Conductivity Mass Balance method. The ratio of baseflow discharge to total discharge was used to track the timing of when wetland drainage became a substantial component of baseflow. The timing of substantial baseflow was then related to the timing and magnitude of different hydroclimatic processes (precipitation, snowpack, snowmelt, and streamflow) to determine which processes have the greatest influence on wetland drainage. Four hydrologically distinct years were examined: 2018 (dry), 2019 (wet), 2020 (average), and 2021 (dry). Results show that the timing of substantial baseflow in the wet year (2019) occurred between 40 – 60 days later than the timing of substantial baseflow in the dry years (2018 and 2021), suggesting that wetland drainage plays a relatively larger role in maintaining streamflow in dry years. While wetland drainage plays an important role in maintaining streamflow in every year, the relative importance of wetland drainage varies each year due to variability in hydroclimate processes. Dry years, which rely on wetland drainage to maintain streamflow earlier in the year, will have a greater reliance on groundwater, because groundwater provides a constant source of water year-round and buffers streamflow. Mountain wetlands that are supported by groundwater may be potentially more resilient to the effects of hydroclimatic variability if the groundwater supply that they are connected to is sufficiently large enough to support them. Given that wetland drainage is important in the SBB, it may also be important for maintaining streamflow in other high-elevation, snowmelt- dominated, headwater watersheds.